GOOD CORPORATE GOVERNANCE PENGARUHNYA TERHADAP KINERJA KEUANGAN - FRIYANTO - (STIE Indonesia Malang, 2023)
The study aims to determine and analyze the partial influence of Good Corporate Governance (Managerial Ownership, Independent Board of Commissioners and Audit Committee) on the Financial Performance (Studies on Manufacturing Companies in the Food and Beverage Sector Listed on the Indonesia Stock Exchange in 2017 – 2020). The sample in this study is the financial statements of 8 (eight) companies in the food and beverage sector which are listed on the Indonesia Stock Exchange in 2017- 2020, with a total of 32 financial reports selected using a purposive sampling technique. The results of partial hypothesis testing state that Managerial Ownership has a significant effect on Financial Performance. The Independent Board of Commissioners has no significant positive effect on Financial Performance and the Audit Committee has no significant positive effect on Financial Performance.Keyword : Good Corporate Governance and Financial Performance